Enhancing retail operations: Dynamic fulfilment strategies in Omnichannel retail - İskender, Hümeysa; Dayanıklı, Sinem; Kökçam, Abdullah Hulusi; Stević, Željko; Turgay, Safiye; Baydaş, Mahmut; Bunevska Talevska, Jasmina (Serbian Journal of Management, 2024)
This study explores the trend of in-store fulfillment in omnichannel retail, where nearby store inventories are utilized for online order fulfillment. This model presents advantages such as faster delivery, cost reduction, improved stock management, increased sales, and enhanced customer satisfaction. Operational challenges include determining the optimal fulfillment location for online orders. Investigating a retailer with online and brick-and-mortar stores, this paper addresses dynamic order fulfillment decisions considering customer demand and shipping cost uncertainties. The study employs Stochastic Dynamic Programming for shorter periods and the Genetic Algorithm for longer periods, revealing that the Genetic Algorithm provides solutions closely approximating optimal.
Keywords: decision-making; dynamic programming; genetic algorithm; omnichannel marketing; order fulfillment